On the Field‐Aligned Beam Thermal Energy. Issue 11 (8th November 2013) - Meziane, K.; Hamza, A. M.; Wilber, M.; Mazelle, C.; Lee, M. A.
<x xml:space="preserve">Abstract</x> [1] The parallel and perpendicular reduced distribution functions of field‐aligned beams (FABs) observed upstream of the Earth's bow shock using the Cluster spacecrafts are examined. A previous study revealed that FABs, observed in oblique shock geometries, exhibit reduced distribution functions with high‐energy tails. A selection of FABs with weak‐energy tails are considered, and the associated reduced distributions are fit with Maxwellians. First, we have found that the FABs full width at half maximum (FWHM), σ∥ and σ⊥ derived from the fit, are linearly correlated with the solar wind speed (or equivalently to solar wind temperature). Moreover, the parallel beam σ∥ has a very weak dependence upon the beam parallel speed which reflects the shock geometry; we have found that σ∥∼0.23Vsw. In contrast, we have found that the perpendicular beam σ⊥, in the range of beam speeds investigated, depends on the shock geometry. These new results indicate that the parallel σ∥ is essentially controlled by the solar wind while the shock geometry plays, along with the solar wind, a role in the perpendicular σ⊥. These results also put some strong constraints on theoretical models as far as field‐aligned beam production mechanisms are concerned. One potential explanation for the significant perpendicular broadening of the FAB distribution reported in this study could be the presence of kinetic Alfvèn (or/and whistler) turbulence at the shock.